Study on decomposition of litter under canoppy of natural - restored secodary foest at Me Linh station for biodiverity - Tan, Le Dong; Chung, Do Hoang (Academia Journal of Biology, 2012)
Me Linh station for biodiversity is a unit of Institute of Ecology and Biological Resources, Vietnam Academy of Scientific and Technology. It locates at Ngoc Thanh community Phuc Yen town and Vinh Phuc province. It has total of area 170.3 ha, in which consist of secondary forest and shrubs and grassland that were recovered after logging and clearly cutting for plantation. There are four sites of secondary forest (including ML1, ML2, ML4 and ML4) were selected to study on decomposition of litter. Composition of dominant tree species in the sites are Toxicodendron succedanea, Canarium parvum and Cratoxylum polyanthum in ML1; Toxicodendron succedanea, Canarium parvum and Cratoxylum polyanthum in ML2; Styrax tonkinensis, Macaranga denticulata and Toxicodendron succedanea in ML4; Saraca dives, Bischofia javanica, Diospyros in ML4; Styrax tonkinensis, Choerospondias sp. in ML3. The results showed that: Mass of average of the litter in the secondary forest is 9.78 tons/ha; in which proportion of leaves is more than branches (mass of leaves is 7.64 tons/ha, appropriately 76.39% and branches is 2.23 tons/ha, appropriately 23.61%). There are different on mass of the litter between sites but not large, changes from 8.30 tan/ha in ML1 to 11.60 tons/ha in ML4. The records in field showed that composition of species is one of main reasons effecting to ratio leave/branch of the litter in studied sites. Process of decomposition of litter is happen continuous. After 12 months, the quantify of decomposed litter in ML1 is largest with 94.80% and smallest in the ML4 with 62.86%. There is different on dynamic of decomposition of litter between sites. This is shown by data of the distribution of number of the decomposed litter between periods of time sampling. The amount of decomposed litter in dry season is more than in rain season in all sites. According to coefficient kL year-1, rate of decomposition of litter is arranged in order of following: ML4 < ML2 < ML3 < ML1.